Wet chemical synthesis of metal oxide nanoparticles: a review - Nikam, A. V.; Bhagavatula L. V. Prasad; Kulkarni, A. A. (Crystengcomm, 2018)
Metal oxide nanoparticles are an important class of nanomaterials that have found several applications in science and technology. Through wet chemical synthesis, it is possible to achieve selective surface structures, phases, shapes, and sizes of metal oxide nanoparticles, leading to a set of desired properties. Wet chemical synthesis routes allow fine tuning of the reaction conditions (temperature, concentration of substrate, additives or surfactants, pH, etc.) to afford the desired nanomaterials. In this review article, we highlight recent developments in the wet chemical synthesis of metal oxide nanoparticles to provide great control over the quality of the obtained nanomaterials. The review critically evaluates the different wet chemical methods for scalable production of metal oxide nanoparticles to satisfy the growing industrial demand for nanomaterials. Special attention is paid to continuous flow synthesis of metal oxide nanoparticles.

Telescoped sequence of exothermic and endothermic reactions in multistep flow synthesis - Sharma, Y.; Nikam, A. V.; Kulkarni, A. A. (Organic Process Research and Development, 2019)
A multistep sequential flow synthesis of isopropyl phenol is demonstrated, involving 4-step exothermic, endothermic, and temperature sensitive reactions such as nitration, reduction, diazotization, and high temperature hydrolysis. Nitration of cumene with fuming nitric acid produces 2- and 4-nitrocumene which are converted into respective cumidines by the hydrogenation using Pd/Ni catalyst in H-cube with gravity separation. Hydrolysis of in situ generated diazonium salts in the boiling acidic conditions is carried out using integration of flow and microwave-assisted synthesis. 58% of 4-isopropyl phenol was obtained. The sequential flow synthesis can be applied to synthesize other organic compounds involving this specific sequence of reactions.